John Constantine, Hellblazer. Volume 2, The best version of you - Spurrier, Simon (Sandman Universe, 2021)
"In London, John Constantine is up to his usual antics. The adventures continue, quite dark and still twisted. Will he protect a group of British fishermen from an ancient merwoman? Or stop a disgraced royal from unleashing a bloodthirsty horror? There's really only one way to find out"--